Implementing the PEEC technique through classroom action research: A strategy to mitigate adad–ma‘dud errors in beginner-level Arabic writing - Sa'diyah, Halimatus; Rusuly, Usfiyatur; Saputri, Intan Nur Fauziah (STAI Auliaurrasyidin Tembilahan, 2026)
Mastering writing skills is a fundamental yet challenging aspect of beginner-level Arabic language acquisition, particularly in applying complex grammatical constructs such as adad–ma‘dūd (numeral-noun agreement). Conventional teacher-centered correction methods often fail to facilitate the deep processing required for rule internalization. This classroom action research (CAR) proposes the PEEC (Peer Editing and Error Correction) technique, a novel collaborative strategy integrating peer discussion with immediate corrective feedback to address this pedagogical gap. Conducted over two cycles with 36 first-year students in an intensive Arabic program at a state Islamic university in Malang, the study employed observation, writing tests, and document analysis of student drafts. Results demonstrated significant improvement in writing accuracy. The number of students achieving the mastery criterion rose from 12 (33.33%; average score: 61) in the pre-cycle, to 23 (63.89%; average: 73) in cycle I, and to 32 (88.89%; average: 84) in cycle II. This represents a 55.56% increase in completion rate and a 23-point average score gain, with marked enhancement in adad–ma‘dūd application. The findings confirm PEEC as an effective intervention for developing beginner Arabic writing proficiency, warranting further exploration in diverse instructional contexts.